SUSTAINABLE SUPPLY CHAIN MANAGEMENT AS A FACTOR IN MINIMIZING OPERATIONAL RISKS - Buryk, Zoriana; Tadeoshchuk, Olha (Public Management and Policy, 2026)
In today’s environment of global instability, tightening environmental standards, and increasing corporate social responsibility, traditional supply chain management models focused solely on cost minimization are losing their effectiveness. Operational risks associated with logistical disruptions, reputational losses, and regulatory sanctions require management to transition to the concept of Sustainable Supply Chain Management (SSCM). Integrating ESG (Environmental, Social, Governance) principles into logistical processes is becoming not only an ethical issue but also a strategic tool for ensuring the operational resilience of an enterprise in the context of post-crisis economic recovery. The Purpose of the Article is the theoretical justification and development of practical recommendations for using sustainable supply chain management tools as an effective mechanism for minimizing operational risks in a dynamic market environment. The study employs general scientific methods of analysis and synthesis to refine the conceptual apparatus of SSCM, the categorization method for classifying operational risks, and a logical-analytical approach to identify the relationship between socio-environmental responsibility and the economic security of business entities. It is proven that the integration of sustainable approaches into the administrative management system allows for the transformation of the supply chain from a linear structure into a flexible ecosystem. It is established that administrative control within SSCM should be based on the principles of transparency and continuous auditing of the product life cycle. It is determined that the primary levers for minimizing operational risks include the implementation of “green” supplier audits, digitalization of resource flow monitoring, and compliance with social labor standards. It is substantiated that social management within SSCM contributes to reducing reputational risks and strengthening stakeholder loyalty by establishing ethical standards for interaction with contractors. The author proposes an integrated model for evaluating the effectiveness of sustainable supply chains, which considers not only economic indicators but also the level of environmental impact and social inclusivity, allowing for the early identification of potential threats to operational activities. Scientific Novelty lies in the improvement of organizational and managerial tools for risk minimization by combining administrative control methods with the principles of social responsibility within a unified sustainable development strategy. The definition of the term “operational resilience of the supply chain” has been further developed as the system’s ability to mitigate external shocks through compliance with environmental and social imperatives. The formulated conclusions and recommendations can be utilized by enterprise managers to improve operational activities, increase investment attractiveness, and adapt business models to the requirements of European legislation in the field of sustainable development.